Demographic change in Switzerland: Impacts on economic growth in an Overlapping Generations Model - Luisa-Marie Hauser; Carsten-Henning Schlag; André Wolf (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2020)
This paper analyses the macroeconomic implications of a future shift in the age structure of the Swiss population. It estimates the long-run effects for Swiss GDP growth and its components in an Overlapping Generations Model (OLG model). Recent population projections by the Federal Statistical Office (FSO) serve as a basis. To document the sensitivity of the results with respect to the demographic assumptions, simulations were undertaken for a range of alternative scenarios concerning fertility, migration and agespecific labor supply. Our projections over the time horizon 2018-2060 document a significant loss in terms of economic growth in both absolute and per capita terms. According to our simulations, this would primarily affect the income of the middle-aged age groups. Likewise, the process of ageing would have consequences for the composition of Swiss GDP: the share of government spending on domestic value added is simulated to increase, due to its demography-related components. A sensitivity analysis reveals that more favourable assumptions concerning future net immigration, fertility and labor market participation could mitigate, but not fully compensate these trends.
Keywords: J11; C68; E37; 330; Ageing; OLG-models; Long-term GDP forecasts; Switzerland